Pengembangan Beton Precast Modular Berbasis Kearifan Lokal Mapalus Untuk Hunian Masyarakat Berpendapatan Rendah. - Nendu, Auradea; Timbuleng, Abelita; Tunas, Meitrisia; Danel, Marselino; Peginusa, Stefani Switly; Assa, Vicky Alexander; Pinasang, Denny Boy; Mantiri, Hellen Grace (Jurnal Teknik Sipil Terapan, 2026)
Abstrak The high housing backlog and the unsustainability of conventional construction methods remain major obstacles in providing decent housing for Low-Income Communities (MBR). This study aims to examine the development of modular precast concrete based on Mapalus local wisdom for low-income community housing, utilizing a combination of the RUSPIN framework and an innovative type 36 modular precast wall panel. The research method employs a quantitative comparative analysis to evaluate technical, cost, and time efficiency in field execution. The results indicate that implementing these modular precast concrete components reduces construction costs to IDR 182,690,460, which is more economical than the conventional method at IDR 197,908,671. Furthermore, the project scheduling is significantly shortened from 107 days to only 46 working days. The main advantage of this system lies in its lightweight components and dry connections (bolts), making it highly adaptive for integration with the Mapalus mutual cooperation social engineering system in Minahasa without heavy equipment dependency. The critical conclusion of this research proves that developing modular precast concrete technology synchronized with local wisdom effectively serves as a stimulant solution for fast, affordable, and mass MBR housing delivery. Keywords: low-income communities, mapalus, modular precast concrete, ruspin